A comparative analysis of the range of medicines applied for the cerebral palsy pharmacotherapy in Ukraine by the British National Formulary - Парамош, Олена Вікторівна (ScienceRise: Pharmaceutical Science, 2016)
Aim. The improvement of the range of medicines applied for the cerebral palsy treatment in Ukraine. Metthods. System analysis, marketing research, expert estimation of remedies. Results. Pharmacuetical market of Ukraine needs to be expanded by including the actual remedies for the cerebral palsy treatment: Oxcarbazepine from the antiepileptic remedies pharmacotherapeutic group and Atomoxetine from the group of the psycoanaleptics, which are being used in British lists. Four muscle relaxants, available in the British children's formulary: Xeomin, Azalyur, Bocautur and Damdrolene Sodium are absent in Ukraine. Conclusion. 34 drugs from the Ukraine State drug formulary (2016), State drug register (2016), the British children's formulary (April, 2016), and the British national formulary (April, 2016) as common objects for the study of the modern range of medicines in developed countries, were analyzed for comparative study of pharmaceutical market of remedied applied for the cerebral palsy treatment. The differential analysis by specific pharmacological groups is presented by muscle relaxants, which include 8 remedies, antiepileptic drugs – 12, psychoanaleptics – 12, and other remedies affecting nervous system – 2. To compare, antiepileptic drug Oxcarbazepine and Atomoxetine from the group of the psycoanaleptics are absent in Ukraine. Muscle relaxants: Suxamethonium, Pipekuroniyu bromide, Tolperizon, and psychoanaleptics that are not included into the British formularies: Caffeine, Vinpocetine, Mebicar, Phenybutun are used in Ukraine simultaneously